A high-efficiency Fe2O3@Microalgae composite for heavy metal removal from aqueous solution. (February 2020) - Shen, Li; Wang, Junjun; Li, Zhanfei; Fan, Ling; Chen, Ran; Wu, Xueling; Li, Jiaokun; Zeng, Weimin
Abstract: In recent years, the application of algae and metal oxides to treat heavy metal wastewaters has attracted considerable attention. However, algae are difficult to recover due to their low density, which will cause secondary pollution and limit its development in the treatment process. In this paper, metal oxide (Fe2 O3 ) as an adsorptive material is used to form a composite material with algae, which not only can achieve the purpose of immobilizing microalgae but can also improve the adsorption effect. We controlled the synthesis temperature of the Fe2 O3 to reach a good immobilization effect for microalgae, and the adsorption capacity of the composite material (Fe2 O3 @Microalgae) was tested. The results showed that the adsorption of Fe2 O3 @Microalgae for Cr(VI), Cu(II), Pb(II) and Cd(II) followed the pseudo second-order model (R 2 > 0.99). The equilibrium data of Fe2 O3 @Microalgae agreed well with the Langmuir adsorption isotherm model and the maximum adsorption capacity of Fe2 O3 @Microalgae was higher than that of microalgae or commercial Fe2 O3 alone. The adsorption capacity for metal ions can be ranked in the following order: Cr(VI) (69.77 mg/g) > Pb(II) (62.63 mg/g) > Cd(II) (42.12 mg/g) > Cu(II) (38.68 mg/g). Functional groups, such as OH and COOH on the adsorbent surface, were involved in the adsorption process. Therefore, Fe2 O3 @Microalgae not only achieved the purpose of immobilizing microalgae, but also combined the material with the biosorbent, thereby enhancing the adsorption effect. The biocomposite is thus has potential as an adsorbent for sewage treatment.